Slang in the Comment Column of TikTok Social Media Account @FADILJAIDI: Bahasa Gaul dalam Kolom Komentar Media Sosial TikTok Akun @FADILJAIDI - Isna; Fahruddin; Amirudin Rahim (Jurnal Pesastra (Pendidikan Bahasa dan Sastra), 2026)
This study aims to identify the forms, contextual meanings, communicative functions, and scientific contribution of slang used in the comment column of the TikTok account @fadiljaidi. The study employed a qualitative descriptive design with a sociolinguistic and digital discourse perspective. The data consisted of documented comment excerpts containing slang in several @fadiljaidi videos uploaded in November 2025. Data were collected through observation, documentation, screenshot archiving, and note-taking. Data analysis was conducted by reducing the corpus, coding slang units, classifying morphological forms, interpreting contextual meanings, and comparing the findings with prior studies and relevant theories. The results show that slang appears in acronyms, abbreviations, contractions, clippings, reversal forms, informal pronouns, phonological variation, and phatic expressions. The findings also reveal four dominant functions: creating intimacy, producing humor, evaluating the creator's action, and strengthening digital group identity. The study concludes that slang in TikTok comments is not merely a nonstandard language practice but a patterned form of digital vernacular creativity. The scientific contribution of this study lies in the typological-functional synthesis of TikTok slang that links word-formation processes, contextual meaning, and digital social affiliation in Indonesian sociolinguistic studies.